Analytical study on one-way reinforced concrete beam-slab sub-structures under compressive arch action and catenary action. (1st March 2020) - Kang, Shao-Bo; Wang, Shan; Gao, Shan
Highlights: An analytical model is developed for compressive arch action and catenary action in one-way reinforced concrete beam-slab sub-structures. The analytical model yields reasonably accurate estimations of the load capacity and force-transfer mechanism of one-way beam-slab sub-structures. Abstract: In case of accidental loading, compressive arch action and catenary action in beams and slabs can be mobilised to resist progressive collapse of reinforced concrete structures. Analytical models have been proposed for reinforced concrete beam-column sub-assemblages under compressive arch action and catenary action. Nonetheless, the effects of the slab on load resistance and deformation capacity of one-way beam-slab sub-structures have not been fully investigated. This paper presents a study on the structural behaviour of one-way beam-slab sub-structures subjected to compressive arch action and subsequent catenary action. In the study, an analytical model is developed to predict the load-displacement relationship and the axial force-displacement relationship of sub-structures. The model is developed in accordance with rigid-plastic assumption. Compatibility, equilibrium and constitutive models for steel reinforcement and concrete are taken into account in the model. Hogging and sagging moments are calculated by taking moments about the plastic centres of beam-slab sub-structures. The model is validated against published test data and reasonably good accuracy is obtained in terms of the load resistances under compressive arch action and catenary action. The variation of bending moments, neutral axis depths and steel strains can also be obtained through the analytical model. The model is then used for parametric study of the effects of longitudinal reinforcement, slab width, and thickness on compressive arch action and catenary action. The parametric study shows that the cross-sectional area of longitudinal reinforcement in the slab affects the catenary action capacity and the width and thickness of the slab affects the deformation capacity of one-way beam-slab sub-structures. Finally, conclusions are drawn from the analytical study which can be used in the design of one-way beam-slab sub-structures against progressive collapse.